Highlighting the role of biota in feedback loops from tundra ecosystems to the atmosphere - Schmidt, Niels M.; Barrio, Isabel C.; Kristensen, Jeppe A.; López-Blanco, Efrén; van Beest, Floris M. (Frontiers in Environmental Science, 2024)
The rapid climatic and environmental changes observed in the Arctic and across the globe in general call for reliable model projections. In recent years our understanding of ongoing and future changes through ecosystem modelling has increased tremendously. Yet, most ecosystem models do not consider many of the feedback loops at play in natural ecosystems. Particularly those influenced by biota, beyond vegetation and to some extent microbes, are often neglected. As a first step towards a better integration of biotic influences into ecosystem models, we provide a broad overview of the various ways biota may influence feedback loops between the high-latitude biosphere and the atmosphere. We focus specifically on three key feedback loops between tundra and atmosphere (carbon dynamics, albedo and permafrost thaw) and the influences of three key ecosystem compartments (vegetation, decomposers and herbivores) on these. The influences of biota on ecosystem feedback loops are multifaceted and may appear patchy in both space and time. However, biota may still play important roles in modulating ecosystem feedback loops, and by including these dynamics into ecosystem models, magnitude, accuracy and credibility of model projections are likely to improve.